The effect of applying IFRS 16 (lease contracts) on financial statements and financial leverage (Empirical study on Al-Sharq Bank) - الداود صالح; نواف فخر (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The aim of the research is to demonstrate the effect of applying IFRS 16 (lease contracts) on financial statements and financial leverage.The researcher adopted the descriptive analytical approach by forming a knowledge framework through periodicals and researches to describe the relationship between the two variables of the study, and the experimental approach by applying the standard in Bank Al-Sharq for the year 2018 and the analytical comparison after capitalization to find out the impact that the application of the standard plays on the net profit, the values of assets and liabilities, and financial leverage from increasing and spin. The research reached a set of results, the most important of which are: The application of International Financial Reporting Standard 16 (lease contracts) affects the net profit at Al-Sharq Bank. The application of International Financial Reporting Standard 16 (lease contracts) affects the total assets and total liabilities of Bank Al-Sharq, as the application led to an increase in fixed assets, total assets, and an increase in long-term liabilities and total liabilities in the statement of financial position. The application of IFRS 16 (lease contracts) affects financial leverage. Where the implementation of the standard led to a higher degree of leverage.